Validation and Utilization of a Clinical Next-Generation Sequencing Panel for Selected Cardiovascular Disorders - Celestino-Soper, Patrícia B. S.; Gao, Hongyu; Lynnes, Ty C.; Lin, Hai; Liu, Yunlong; Spoonamore, Katherine G.; Chen, Peng-Sheng; Vatta, Matteo (Frontiers in Cardiovascular Medicine, 2017)
The development of high throughput technologies such as next generation sequencing (NGS) has allowed for thousands of DNA loci to be interrogated simultaneously in a fast and economical method for the detection of clinically deleterious variants. Whenever a clinical diagnosis is known, a targeted NGS approach involving the use of disease-specific gene panels can be employed. This approach is often valuable as it allows for a more specific and clinically relevant interpretation of results. Here we describe the customization, validation, and utilization of a commercially available targeted enrichment platform for the scalability of clinical diagnostic cardiovascular genetic tests, including the design of the gene panels, the technical parameters for the quality assurance (QA) and quality control (QC), the customization of the bioinformatics pipeline, and the post-bioinformatics analysis procedures. Regions of poor base coverage were detected and targeted by Sanger sequencing as needed. All panels were successfully validated using genotype-known DNA samples either commercially available or from research subjects previously tested in outside clinical laboratories. In our experience utilizing several of the sub-panels in a clinical setting with 33 real-life cardiovascular patients we found that 20% of tests requested were reported to have at least one pathogenic or likely pathogenic variant that could explain the patient phenotype. For each of these patients, the positive results may aid the clinical team and the patients in best developing a disease management plan and in identifying relatives at risk.